Effects of Erosion and Deposition on Constraining Vertical Slip Rates of Thrust Faults: A Case Study of the Minle–Damaying Fault in the North Qilian Shan, NE Tibetan Plateau - Liu, Qingri; Zhang, Huiping; Li, Youli; Huang, Feipeng; Zhao, Xudong; Lei, Jinghao; Xin, Weilin; Xiong, Jianguo; Zhang, Peizhen (Frontiers in Earth Science, 2021)
The height of a thrust-fault scarp on a fluvial terrace would be modified due to erosion and deposition, and these surface processes can also influence the dating of terraces. Under such circumstances, the vertical slip rate of a fault can be misestimated due to the inaccurate displacement and/or abandonment age of the terrace. In this contribution, considering the effect of erosion and deposition on fault scarps, we re-constrained the vertical slip rate of the west end of the Minle-Damaying Fault (MDF), one of the thrusts in the north margin of the Qilian Shan that marks the northeastern edge of the Tibetan Plateau. In addition, we tried to explore a more reliable method for obtaining the vertical fault displacement and the abandonment age of terraces with AMS 14C dating. The Monte Carlo simulation method was used to estimate the uncertainties of fault displacements and vertical slip rates. Based on comparative analysis, the dating sample from the fluvial sand layer underlying the thickest loess in the footwall was suggested to best represent the abandonment age of the terrace, and the fluvial gravel layer could better preserve the original vertical fault displacement compared with the surface layer. Using the most reliable ages and vertical offsets, the vertical slip rate of the MDF was estimated to be 0.25-0.28 mm/a since 42.3 ± 0.5 ka (T10) and 0.14-0.24 mm/a since 16.1 ± 0.2 ka (T7). The difference between the wrong vertical slip rate and the right one can even reach an order of magnitude. We also suggest that if the built measuring profile is long enough, the uncertainties in the height of a surface scarp would be better constrained and the result can also be taken as the vertical fault displacement. Furthermore, the consistency of chronology with stratigraphic sequence or with terrace sequence are also key to constraining the abandonment ages of terraces. The fault activity at the study site is weaker than that in the middle and east segments of the MDF, which is likely due to its end position.